Cultural Influences on Corporate Social Responsibility - Mathew, Jain; Kumar, Jyothi (Ushus Journal of Business Management, 2010)
To date, research that demonstrates what Corporate Social Responsibility (CSR) actually means in terms of policies and practices in the pharmaceutical industries is scarce. Similarly, research that shows understanding or compares the cultural influences of the East and the West on CSR in the pharmaceutical industry is also scarce.